Features of the impact of COVID-19 and sanctions on the development of the tourism industry of the North Caucasus macro-region - T. A. Kulagovskaya; G. I. Panaedova; D. S. Grigoriev (Вестник Северо-Кавказского федерального университета, 2023)
The article analyzes current issues of the impact on the tourism industry of the North Caucasus macro-region of the consequences of the COVID-19 pandemic and the imposed sanctions against the Russian Federation. As the first hypothesis of the study, the authors assume that the imposed economic sanctions had more negative impact than the coronavirus pandemic. The second hypothesis of this study is the possibility of positive consequences of crises, since the cyclical development of economic processes indicates that the crisis phenomenon is traditionally followed by a rise.